Primary school factors associated with children’s physical activity in the outdoor environment: a mixed-methods study to inform the development of a quality of outdoor environment survey - Woolley, Kay (2022)
Recent data from the National Child Measurement Programme in England (2019-2020) shows that over a third of children aged 10-11 and more than a fifth of children aged 4-5 are overweight or obese. There is a need to implement strategies to reduce this prevalence in children in order to limit associated health problems now and in the future. Physical activity is thought to play a crucial role in the management of childhood obesity. However, despite the considerable benefits to children’s health, proportions of young people meeting WHO guidelines for PA levels are low across the world. Schools are thought to be ideally placed to promote children’s PA and may be able to utilise the outdoor environment for encouraging children to be active.